The architects' handbook - Pickard, Quentin (Blackwell Science, 2002)
The Architects' Handbook provides a comprehensive range of visual and technical information covering the great majority of building types likely to be encountered by architects, designers, building surveyors and others involved in the construction industry. It is organised by building type and concentrates very much on practical examples.